Persepsi Guru tentang Kompetensi Kepribadian Tenaga Administrasi Sekolah di SMK Negeri Kota Payakumbuh - Lendi, Elsia Syahida; Adi, Nelfia (Journal of Practice Learning and Educational Development, 2023)
This study aims to dig up information about teachers perceptions about the personality competence of school administration staff at SMK Negeri Payakumbuh in terms of having integrity and noble character, having a work ethic, self-control, having self-confidence, having flexibility, having thoroughness, having discipline, have creativity and innovation as well as have responsibility. This type of research is descriptive quantitative. The population of this research is teachers of SMK Negeri Payakumbuh, totaling 454 people. A sample of 86 people was taken using a proportional stratified random sampling technique. The data collection instrument was a Likert scale model questionnaire with five answer choices, that is always (SL), often (SR), rarely (JR), sometimes (KD), never (TP). This research questionnaire has been tested for validity and reliability, then the data is processed using the average formula (mean). The results showed that teachers perceptions on aspects 1) have integrity and noble character with an average score of 4.44 are in the capable category, 2) have a work ethic with an average score of 4.27 in the capable category, 3) self-control with an average score of 3.98 in the capable category, 4) having confidence with an average score of 4.21 in the capable category, 5) having flexibility with an average score of 4.06 in the capable category, 6) has accuracy with an average score of 4.27 in the capable category, 7) discipline with an average score of 3.88 is in the capable category, 8) has creativity and innovation with an average score of 4.10 in the capable category and 9) have responsibility with an average score of 4.17 in the capable category. Thus it can be concluded that the teacher's perception of the personality competence of school administration staff at SMK Negeri Payakumbuh is in the capable category with an average score of 4.15. Based on these results, the authors suggest that the personality competencies of school administration staff at SMK Negeri Payakumbuh in schools are maintained and need to be improved so that they can improve the personality competencies of school administration staff.